2021
DOI: 10.1080/02607476.2021.1904777
|View full text |Cite
|
Sign up to set email alerts
|

Teachers as learners – a qualitative exploration of pre-service and in-service teachers’ continuous learning community OpenDigi

Abstract: This study explores pre-service and in-service teachers' experiences in working as a learning community. Pre-service teachers (N = 60) and teacher educators (N = 9) from a Finnish university and inservice teachers (N = 27) from four local comprehensive schools worked together over six months. The teachers-as-learners continuous learning model was created and implemented in practice. The participants' written reflections were collected to explore what they learned, what challenges they experienced and how they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The synchronous setup allows both teachers and students to stay productive despite the limitations. To [48] on their espoused teachers-as-learners continuous learning model, teachers, with the most moves, with the knowledge of education technology, have the most options. These options, in turn can have the most significant degree of influence on their students.…”
Section: B Discussionmentioning
confidence: 99%
“…The synchronous setup allows both teachers and students to stay productive despite the limitations. To [48] on their espoused teachers-as-learners continuous learning model, teachers, with the most moves, with the knowledge of education technology, have the most options. These options, in turn can have the most significant degree of influence on their students.…”
Section: B Discussionmentioning
confidence: 99%
“…Scholars have studied pre-service teachers and student teachers as individuals and investigated how they construct their teacher identity (Deng et al, 2018; Iversen, 2021; Katwijk et al, 2021; Laletas & Reupert, 2016; Näykki et al, 2021; Yuan et al, 2019). For example, a research project on secondary pre-service teachers’ responsibility to care for students found that neither pedagogy nor discipline strategies would be effective without care, which raises training implications and suggestions for future research into training these teachers (Laletas & Reupert, 2016).…”
Section: Research Literature On Pre-service Teachersmentioning
confidence: 99%
“…Teachers have dual responsibilities, to not only improve their own socio-emotional competence, but also to support the development of their students' competences from the very beginning of their career (Hagenauer et al, 2015). Professional development in terms of socio-emotional competence is a longlasting process, starting from initial teacher education and continuing during the teaching career (Richter et al, 2011;Niemi and Nevgi, 2014;Kyndt et al, 2016;Häkkinen et al, 2017;Näykki et al, 2021a). Particularly teaching practice offers ideal opportunities and building blocks for professional and socioemotional competence development (Colasante, 2011;Hascher and Hagenauer, 2016).…”
Section: Introductionmentioning
confidence: 99%